On the mechanism of photocatalytic reactions with eosin Y - Majek, Michal; Filace, Fabiana; Wangelin, Axel Jacobi von (Beilstein Journal of Organic Chemistry, 2014)
A combined spectroscopic, synthetic, and apparative study has allowed a more detailed mechanistic rationalization of several recently reported eosin Y-catalyzed aromatic substitutions at arenediazonium salts. The operation of rapid acid–base equilibria, direct photolysis pathways, and radical chain reactions has been discussed on the basis of pH, solvent polarity, lamp type, absorption properties, and quantum yields. Determination of the latter proved to be an especially valuable tool for the distinction between radical chain and photocatalytic reactions.
Keywords: mechanism; organocatalysis; photocatalysis; photoredox catalysis; quantum yields; visible light